Exploring sustainable urban automobility transitions : a transdisciplinary inquiry into the case of an isolated enclave in Cape Town, the South Peninsula - Henshilwood, Elizabeth (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.